2019
DOI: 10.1038/s41419-019-1420-9
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-kynurenine pathway attenuates β-catenin-dependent pro-parasitic role of STING-TICAM2-IRF3-IDO1 signalosome in Toxoplasma gondii infection

Abstract: Recent studies have documented the diverse role of host immunity in infection by the protozoan parasite, Toxoplasma gondii. However, the contribution of the β-catenin pathway in this process has not been explored. Here, we show that AKT-mediated phosphorylated β-catenin supports T. gondii multiplication which is arrested in the deficiency of its phosphorylation domain at S552 position. The β-catenin-TCF4 protein complex binds to the promoter region of IRF3 gene and initiates its transcription, which was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
(60 reference statements)
1
26
0
Order By: Relevance
“…IDO, in particular, is associated with infection and induced by IFN type I/II production, prostaglandins as well as microbial components [35,36]. Because pathogens are either tryptophan autotrophs (fully depending on host tryptophan), such as T. gondii and the mouse chlamydia strain, or at least benefit from host tryptophan for their development or growth, the host immune response upregulates IDO, decreasing its availability to pathogens [37][38][39]. Additionally, the metabolites arising from tryptophan degradation have antimicrobial effects themselves, thereby aiding in host-defense [40].…”
Section: Tryptophanmentioning
confidence: 99%
“…IDO, in particular, is associated with infection and induced by IFN type I/II production, prostaglandins as well as microbial components [35,36]. Because pathogens are either tryptophan autotrophs (fully depending on host tryptophan), such as T. gondii and the mouse chlamydia strain, or at least benefit from host tryptophan for their development or growth, the host immune response upregulates IDO, decreasing its availability to pathogens [37][38][39]. Additionally, the metabolites arising from tryptophan degradation have antimicrobial effects themselves, thereby aiding in host-defense [40].…”
Section: Tryptophanmentioning
confidence: 99%
“…The metabolites in the kynurenine pathway have different anti-and pro-oxidant properties that are essential in the maintenance of cell homeostasis (Han, Beerntsen, & Li, 2007). Among the kynurenine pathway metabolites, xanthurenic acid (XA) was shown to act as an antioxidant in Aedes aegypti midgut during digestion of blood meal (Lima et al, 2012) and kynurenine was shown to prevent Toxoplasma gondii growth through induction of apoptosis (Majumdar et al, 2019). The 3-hydroxyl-Lkynurenine (3-HK), another tryptophan metabolite, is shown to stimulate ROS production (Amaral & Outeiro, 2013;Han et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the requirement of β-catenin in the cGAS/STING mediated activation of the IFN pathway was shown in a reporter assay [119]. This could likely happen through the binding of p-β-catenin Ser552 with IRF3 promoter in association with TCF4, as reported following STING activation in Toxoplasma gondii infection [120]. It is interesting to note, however, that viral interference inhibiting the functions of both GSK-3 and β-catenin has been observed with many DNA viruses-encoded proteins including the hepatitis B virus (HBV) X protein [121], the Epstein-Barr virus (EBV) LMP2A [122,123], the latency-associated nuclear antigen of Kaposi's sarcoma-associated herpesvirus (KSHV) [124], and the US3 protein from HSV-1 [119].…”
Section: Cytosolic Dna Sensorsmentioning
confidence: 82%